Bilingual couples in linguistics : a systematic review of research method - Stępkowska, Agnieszka; Buczek, Katarzyna (Penerbit Universiti Kebangsaan Malaysia, 2024)
The paper spotlights bilingual intermarriage by accentuating germane sociolinguistic studies to date in a comprehensive overview. The fact that couples have been largely marginalized in linguistics has become our motivation for a literature overview to establish the scope and directions of the scholarly development related to bilingualism among couples. With this in mind, we conducted a systematic review of research methods used by scholars who study bilingual couples. We analyzed seventy-seven academic publications in English and Polish. The reviewed works were culled from databases including Web of Science, Google Scholar, ERIC, JSTORE, Science Direct, and Semantic Scholar. We focused on publications in English since the bulk of the relevant literature comes out in this language. In turn our choice of Polish has been dictated by the fact that we have better access to linguistic studies in Polish that are less widely available internationally but enrich our research with original perspectives that may be absent from the English-language literature on the subject.